Co-Expression Network Modeling Identifies Specific Inflammation and Neurological Disease-Related Genes mRNA Modules in Mood Disorder - Yang, Chunxia; Zhang, Kun; Zhang, Aixia; Sun, Ning; Liu, Zhifen; Zhang, Kerang (Frontiers in Genetics, 2022)
Objectives: Mood disorders are a kind of serious mental illness, although its molecular factors involved in the pathophysiology remain unknown. One approach to examine the molecular basis of mood disorders is co-expression network analysis (WGCNA), which is expected to further divide the set of differentially expressed genes into subgroups (i.e. modules) in a more (biologically) meaningful way, fascinating the downstream enrichment analysis. The aim of our study was to identify hub genes in modules in mood disorders by using WGCNA. Methods: Microarray data for expression values of 4311721 mRNA in peripheral blood mononuclear cells drawn from 21MDD, 8 BD, and 24 HC individuals were obtained from GEO (GSE39653); Data for genes with expression in the bottom third for 80% or more of the samples were removed; Then the top 70% most variable genes/probs were selected for WGCNA: 27884 probes representing 21840 genes; orrelation between module genes and mood disorder (MDD+BD vs. HC) were evaluated. Results: About 52% of 27765 genes were found to form 50 co-expression modules with sizes 42~3070. Among the 50 modules, the eignegenes of 2 modules were significantly correlated with mood disorder (p<0.05). The saddlebrown module was found in one of the meta-modules in the network of the 50 eigengenes along with mood disorder, 6 (IER5, NFKBIZ, CITED2, TNF, SERTAD1, ADM) out of 12 differentially expressed genes identified in Savitz et al. were found in the saddlebrown module. Conclusions: We found a significant overlap for 6 hub genes (ADM, CITED2, IER5, NFKBIZ, SERTAD1, TNF) with similar co-expression and dysregulation patterns associated with mood disorder. Overall, our findings support other reports on molecular-level immune dysfunction in mood disorder and provide novel insights into the pathophysiology of mood disorder.